2009
DOI: 10.1109/tcapt.2009.2013980
|View full text |Cite
|
Sign up to set email alerts
|

Pool Boiling Experiments on a Nano-Structured Surface

Abstract: Abstract-The effect of nano-structured surfaces on pool boiling was investigated. Saturated and subcooled pool boiling experiments were performed on a horizontal heater surface coated with vertically aligned multiwalled carbon nanotubes (MWCNTs). MWCNTs were synthesized using the chemical vapor deposition (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(11 citation statements)
references
References 23 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…Ahn et al . 18 and Sathyamurthi et al . 19 reported experimental results of pool boiling in PF5060 fluid on silicon heaters coated with vertically aligned, multi-walled carbon nanotubes (MWCNTs).…”
Section: Wall Heat Flux Controlled Boiling Heat Transfermentioning
confidence: 96%
“…Ahn et al . 18 and Sathyamurthi et al . 19 reported experimental results of pool boiling in PF5060 fluid on silicon heaters coated with vertically aligned, multi-walled carbon nanotubes (MWCNTs).…”
Section: Wall Heat Flux Controlled Boiling Heat Transfermentioning
confidence: 96%
“…Density and length of CNT's are important parameters for its performance in nucleate boiling. Ahn et al [191,192] used CVD technique to coat CNTs on the silicon surface. They coated two different heights of 25 µm (Type A) and 9 µm (Type B).…”
Section: Carbon Based Nanoparticles Coatingsmentioning
confidence: 99%
“…They also measured pool boiling of PF5060 and DI water on 3D micro-structured (staggered cross-meshing) surfaces, and obtained the maximum (not critical) heat fluxes of 27 and 130 W/cm 2 , respectively. Ahn et al (2009) and Sathyamurthi et al ( 2009) reported experimental results of pool boiling in the PF5060 fluid on silicon heaters coated with vertically aligned, multi-walled carbon nanotubes (MWCNTs). Using NWCNTs of layer thicknesses of 9 μm (Type A) and 25 μm (Type B), they found that the critical heat flux was increased by 62% and 58%, respectively.…”
Section: Nano-structured Surfacesmentioning
confidence: 99%